2022
DOI: 10.1021/acs.nanolett.2c02235
|View full text |Cite
|
Sign up to set email alerts
|

Gate-Tunable Resonance State and Screening Effects for Proton-Like Atomic Charge in Graphene

Abstract: The ability to create a robust and well-defined artificial atomic charge in graphene and understand its carrier-dependent electronic properties represents an important goal toward the development of graphene-based quantum devices. Herein, we devise a new pathway toward the atomically precise embodiment of point charges into a graphene lattice by posterior (N) ion implantation into a back-gated graphene device. The N dopant behaves as an in-plane proton-like charge manifested by formation of the characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…Figures 6(a) and (b), along with the results from [47] supports our hypothesis that the observed collapse in [22] is likely attributable to the increase of the cluster extent rather than the magnitude of the Coulomb potential.…”
Section: Atomic Collapsesupporting
confidence: 84%
See 2 more Smart Citations
“…Figures 6(a) and (b), along with the results from [47] supports our hypothesis that the observed collapse in [22] is likely attributable to the increase of the cluster extent rather than the magnitude of the Coulomb potential.…”
Section: Atomic Collapsesupporting
confidence: 84%
“…We observe that as the potential becomes more negative (U ∼ 3 eV), a single bound state splits off from the bottom of the band (∼8.5 eV) and it drifts downwards as the consequence of increasingly attractive potential. The presence of the spectral pole is confirmed by DFT calculations for the nitrogen dopant [47]. A symmetrical effect can be seen for positive (repulsive) potential.…”
Section: Atomic Collapsesupporting
confidence: 54%
See 1 more Smart Citation
“…More so, such capability would allow multiple electrodes to be integrated to contact and control a micron-sized electrical device, e.g. by application of gate voltages [29,[42][43][44][45][46][47][48]. As access with long focal optical microscopes [29] is not easily possible in the DR environment, here, we employ a capacitance-mediated approach [49] for landing the STM tip onto a micron-sized sample.…”
Section: Stm Performance Benchmarkmentioning
confidence: 99%
“…[1][2][3] Previous studies have been demonstrated that single-atom defects in graphene, including an individual C-atom vacancy, H-atom absorption, and N-atom substitution, can efficiently break the local sublattice symmetry of graphene, and hence, give rise to valley-polarized states. [4,5] Topological defects are another kind of atomic defects that are usually ubiquitous and unavoidable in graphene during the epitaxial growth. [6] For each topological defect, the local hexagonal lattice prefers to reconstruct into networks of five-and seven-membered rings, nesting in the intrinsic graphene lattice and leaving no unsatisfied bonds.…”
mentioning
confidence: 99%